Suppressing angiogenesis regulates the irradiation‐induced stimulation on osteoclastogenesis in vitro. Issue 4 (27th October 2017) - Tong, Ling; Zhu, Guoying; Wang, Jianping; Sun, Ruilian; He, Feilong; Zhai, Jianglong
Abstract : Ionizing radiation‐induced bone loss is a potential health concern in radiotherapy, occupational exposure, and astronauts. Although impaired bone vasculature and reduced proliferation of bone‐forming osteoblasts has been implicated in this process, it has not been clearly characterized that whether radiation affects the growth of bone‐resorbing osteoclasts. The molecular crosstalk between different cell populations in the skeletal system has not yet been elucidated in detail, especially between the increased bone resorption at early stage of post‐irradiation and bone marrow‐derived endothelial progenitor cells (BM‐EPCs). In order to further understand the mechanisms involved in radiation‐induced bone loss at the cellular level, we assessed the effects of irradiation on angiogenesis of BM‐EPCs and osteoclastogenesis of receptor activator for nuclear factor‐κB ligand (RANKL)‐stimulated RAW 264.7 cells and crosstalk between these cell populations. We herein found significantly dysfunction of BM‐EPCs in response to irradiation at a dose of 2 Gy, including inhibited proliferation, migration, tube‐forming abilities, and downregulated expression of pro‐angiogenesis vascular endothelial growth factors A (VEGF A). Meanwhile, we observed that irradiation promoted osteoclastogenesis of RANKL‐stimulated RAW 264.7 cells directly or indirectly. These results provide quantitative evidences of irradiation induced osteoclastogenesis at a cellular level, and strongly suggest the involvement of osteoclastogenesis, angiogenesis and crosstalk between bone marrow cells in the radiation‐induced bone loss. This study may provide new insights for the early diagnosis and intervention of bone loss post‐irradiation. Abstract : This study demonstrates that irradiation could not only damage BM‐EPCs angiogenesis by suppressing proliferation, migration, tube‐forming abilities and the expression of pro‐angiogenesis factor VEGF A, but could promote osteoclastogenisis and activation of osteoclasts directly or indirectly.